2023
DOI: 10.7759/cureus.37236
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Community-Level Economic Deprivation and HIV Infection Among Hospital Admissions in Washington, DC

Abstract: Human immunodeficiency virus (HIV) infection is a significant health concern in the United States, affecting 38 million Americans. Despite a recent decline in prevalence, social determinants of health remain an important factor driving infections, particularly among minority populations. However, the relationship between community-level economic deprivation indices and HIV infection among hospital admissions has been understudied in the literature. ObjectivesThis study investigated the association between comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This study confirms the utility of the Distressed Communities Index in predicting important health outcomes because it has successfully predicted mortality after cardiac surgery, 12 COVID-19, 13 limb amputation rates, 14 emergency department visits for firearm injuries, 15 and HIV prevalence among hospital admissions. 16 Although other ophthalmic studies have evaluated state and national emergency department databases, 17 to our knowledge this is the first study to present detailed data on emergency department presentation primarily for DR. As seen in outpatient and survey-based studies, [2][3][4]18 we found race to be predictive of a more advanced presentation of DR, with minority groups being more likely to present to the emergency department for PDR than Whites. As a corollary to previous studies that identified patients with public insurance having lower follow-up rates for PDR after emergency department visits, 19 we found that patients with public insurance were more likely to present to the emergency department for PDR than those with private insurance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study confirms the utility of the Distressed Communities Index in predicting important health outcomes because it has successfully predicted mortality after cardiac surgery, 12 COVID-19, 13 limb amputation rates, 14 emergency department visits for firearm injuries, 15 and HIV prevalence among hospital admissions. 16 Although other ophthalmic studies have evaluated state and national emergency department databases, 17 to our knowledge this is the first study to present detailed data on emergency department presentation primarily for DR. As seen in outpatient and survey-based studies, [2][3][4]18 we found race to be predictive of a more advanced presentation of DR, with minority groups being more likely to present to the emergency department for PDR than Whites. As a corollary to previous studies that identified patients with public insurance having lower follow-up rates for PDR after emergency department visits, 19 we found that patients with public insurance were more likely to present to the emergency department for PDR than those with private insurance.…”
Section: Discussionmentioning
confidence: 96%
“…This study confirms the utility of the Distressed Communities Index in predicting important health outcomes because it has successfully predicted mortality after cardiac surgery, 12 COVID-19, 13 limb amputation rates, 14 emergency department visits for firearm injuries, 15 and HIV prevalence among hospital admissions. 16…”
Section: Discussionmentioning
confidence: 99%